A Hungarian Jurist’s Views on 19th-Century English Juries - Tamás Antal (Journal on European History of Law)
The author presents a brief amendment to the history of British common law by publishing the opinion of a talented Hungarian lawyer on English juries according to his 1870 viewpoint. The new liberal Government sent a young ministry councilor to London to examine the criminal procedure law of that time. After returning home he became one of the flag-bearers of juries in the Austro-Hungarian Monarchy and also made a remarkable influence on the codification process that led to the first Hungarian Code of Criminal Procedure decades later. He armed the constitutional system of the United Kingdom in the second half of the 19th century and the way its legal institutions operated became basic standards for his reform plans as a Minister of Justice in the 1890 s. His name was Desider Szilágyi.